Active material for non-aqueous electrolyte secondary batteries, and non-aqueous electrolyte secondary batteries

JP7943547B2Active Publication Date: 2026-10-30PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2022578330
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-01-29
Filing Date
2022-01-21
Publication Date
2026-10-30
Estimated Expiration
2042-01-21

AI Technical Summary

Benefits of technology

【0008】 本開示の一態様によれば、高レートでの放電容量の低下を抑制することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007943547000002
    Figure 0007943547000002
  • Figure 0007943547000001
    Figure 0007943547000001
Patent Text Reader

Abstract

Provided is an active material that contributes to improved battery rate characteristics. This active material for nonaqueous electrolyte secondary batteries contains a core capable of reversible Li storage / release and contains a compound attached to the surface of the core. The compound is represented by the general formula M1aM2Fb (0.1 ≤ a ≤ 2.2, 2 ≤ b ≤ 6, M1 is at least one element selected from the group consisting of Li, K, and Na, and M2 is at least one element selected from the group consisting of transition metals and Al, Si, B, P, Sn, Ge, Sb, Bi, Mg, Ca, and Sr).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This disclosure relates to an active material for a non-aqueous electrolyte secondary battery, and a non-aqueous electrolyte secondary battery using said active material. [Background technology]

[0002] In non-aqueous electrolyte secondary batteries, the active material can undergo side reactions with the electrolyte, which can reduce battery capacity during charging and discharging. Patent Document 1 discloses a surface-modified lithium-containing composite oxide in which zirconium hydroxide or zirconium oxide and at least one lithium salt selected from the group consisting of Li2ZrF6, Li2TiF6, Li3PO4, Li2SO4, and Li2SO4·H2O are attached to the surface of a lithium-containing composite oxide, for the purpose of improving charge-discharge cycle characteristics, etc. Patent Document 1 also discloses a method for producing a surface-modified lithium-containing composite oxide, which involves mixing a powder of the lithium-containing composite oxide with a solution containing zirconium and a solution containing an ammonium salt, and then heat-treating the mixture. [Prior art documents] [Patent Documents]

[0003] [Patent Document 1] International Publication No. 2014 / 104234 [Overview of the project] [Problems that the invention aims to solve]

[0004] However, after diligent research by the inventors, it was found that depending on the mixing conditions and heat treatment conditions during the manufacturing of surface-modified lithium-containing composite oxides, it may not be possible to suppress the decrease in battery capacity due to charging and discharging. In particular, the discharge capacity may decrease at high rates, and the rate characteristics may deteriorate.

[0005] Therefore, the purpose of this disclosure is to provide an active material that contributes to improving the rate characteristics of a battery. [Means for solving the problem]

[0006] An active material for a non-aqueous electrolyte secondary battery, according to one aspect of this disclosure, comprises a core capable of reversibly intercalating and deintercalating Li, and a compound attached to the surface of the core, wherein the compound has a general formula M1 a M2F b (The formula is characterized by being represented as follows: (0.1 ≤ a ≤ 2.2, 2 ≤ b ≤ 6, M1 is one or more elements selected from the group consisting of Li, K, and Na, and M2 is one or more elements selected from the group consisting of transition metals and Al, Si, B, P, Sn, Ge, Sb, Bi, Mg, Ca, and Sr).

[0007] One embodiment of the present disclosure of a non-aqueous electrolyte secondary battery is characterized by comprising an electrode containing the above-mentioned active material for a non-aqueous electrolyte secondary battery, a counter electrode of the electrode, and a non-aqueous electrolyte. [Effects of the Invention]

[0008] According to one aspect of this disclosure, it is possible to suppress the decrease in discharge capacity at high rates. [Brief explanation of the drawing]

[0009] [Figure 1] This is a longitudinal cross-sectional view of a cylindrical secondary battery, which is an example of an embodiment. [Modes for carrying out the invention]

[0010] By attaching oxides or the like to the surface of the active material, side reactions such as electrolyte decomposition and leaching of transition metals from the positive electrode active material during battery charging and discharging can be suppressed. However, the battery characteristics change depending on the compound attached to the surface. As a result of diligent research, the inventors have found that by attaching oxides or the like to the surface of the active material, the general formula M1 a M2F bWe have discovered that the rate characteristics of secondary batteries can be improved by attaching a compound represented by (0.1≦a≦2.2, 2≦b≦6, M1 is one or more elements selected from the group consisting of Li, K, and Na, and M2 is one or more elements selected from the group consisting of transition metals and Al, Si, B, P, Sn, Ge, Sb, Bi, Mg, Ca, and Sr). It is presumed that this compound specifically suppresses side reactions, thereby protecting the active material and maintaining discharge capacity even at high rates.

[0011] Hereinafter, an example of an embodiment of a non-aqueous electrolyte secondary battery according to this disclosure will be described in detail. In the following, a cylindrical battery in which a wound electrode body is housed in a cylindrical battery case will be given as an example, but the electrode body is not limited to the wound type and may be a laminated type in which multiple positive electrodes and multiple negative electrodes are stacked alternately one by one with a separator in between. Furthermore, the battery case is not limited to a cylindrical shape and may be, for example, rectangular, coin-shaped, etc., or may be a battery case made of a laminate sheet including a metal layer and a resin layer.

[0012] Figure 1 is an axial cross-sectional view of a cylindrical secondary battery 10, which is an example of an embodiment. In the secondary battery 10 shown in Figure 1, an electrode body 14 and a non-aqueous electrolyte (not shown) are housed in an outer casing 15. The electrode body 14 has a wound structure in which a positive electrode 11 and a negative electrode 12 are wound around a separator 13. As the non-aqueous solvent (organic solvent) for the non-aqueous electrolyte, carbonates, lactones, ethers, ketones, esters, etc., can be used, and two or more of these solvents can be mixed and used. When using a mixture of two or more solvents, it is preferable to use a mixed solvent containing a cyclic carbonate and a linear carbonate. For example, ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. can be used as the cyclic carbonate, and dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC), etc. can be used as the linear carbonate. As the electrolyte salt for the non-aqueous electrolyte, LiPF6, LiBF4, LiCF3SO3, etc., and mixtures thereof can be used. The solubility of the electrolyte salt in the non-aqueous solvent can be, for example, 0.5 to 2.0 mol / L. For the sake of explanation below, the side of the sealing body 16 will be referred to as "upper" and the bottom side of the outer casing 15 as "lower".

[0013] The inside of the secondary battery 10 is sealed by closing the open end of the outer casing 15 with the sealing body 16. Insulating plates 17 and 18 are provided above and below the electrode body 14, respectively. The positive electrode lead 19 extends upward through a through hole in the insulating plate 17 and is welded to the lower surface of the filter 22, which is the bottom plate of the sealing body 16. In the secondary battery 10, the cap 26, which is the top plate of the sealing body 16 electrically connected to the filter 22, becomes the positive electrode terminal. On the other hand, the negative electrode lead 20 extends through a through hole in the insulating plate 18 to the bottom side of the outer casing 15 and is welded to the bottom inner surface of the outer casing 15. In the secondary battery 10, the outer casing 15 becomes the negative electrode terminal. If the negative electrode lead 20 is installed at the end, the negative electrode lead 20 extends outside the insulating plate 18 to the bottom side of the outer casing 15 and is welded to the bottom inner surface of the outer casing 15.

[0014] The exterior body 15 is, for example, a bottomed cylindrical metallic exterior can. A gasket 27 is provided between the exterior body 15 and the sealing body 16, and the internal hermeticity of the secondary battery 10 is ensured. The exterior body 15 has a grooved portion 21 for supporting the sealing body 16, which is formed by, for example, pressing the side surface portion from the outside. The grooved portion 21 is preferably formed in an annular shape along the circumferential direction of the exterior body 15, and supports the sealing body 16 via the gasket 27 on its upper surface.

[0015] The sealing body 16 has a filter 22, a lower valve body 23, an insulating member 24, an upper valve body 25, and a cap 26, which are stacked in order from the electrode assembly 14 side. Each member constituting the sealing body 16 has, for example, a disk shape or a ring shape, and each member except the insulating member 24 is electrically connected to each other. The lower valve body 23 and the upper valve body 25 are connected to each other at their respective central portions, and the insulating member 24 is interposed between their respective peripheral edge portions. When the internal pressure of the battery rises due to abnormal heat generation, for example, the lower valve body 23 ruptures, whereby the upper valve body 25 swells toward the cap 26 side and separates from the lower valve body 23, so that the electrical connection between the two is interrupted. When the internal pressure further rises, the upper valve body 25 ruptures, and gas is discharged from the opening 26a of the cap 26.

[0016] Hereinafter, the positive electrode 11, the negative electrode 12, and the separator 13 that constitute the secondary battery 10 will be described. In the following, a case where a predetermined compound is applied to the active material (positive electrode active material) contained in the positive electrode 11 will be described as an example, but the compound may be applied to the active material (negative electrode active material) contained in the negative electrode 12, or the compound may be applied to both the positive electrode active material and the negative electrode active material.

[0017] [Positive Electrode] The positive electrode 11 includes, for example, a positive electrode core body such as a metal foil, and a positive electrode mixture layer formed on the positive electrode core body. For the positive electrode core body, a foil of a metal that is stable in the potential range of the positive electrode such as aluminum, a film having the metal disposed on its surface layer, or the like can be used. The positive electrode mixture layer includes, for example, a positive electrode active material, a binder, a conductive material, and the like. The positive electrode can be produced, for example, by applying a positive electrode mixture slurry containing a positive electrode active material, a binder, a conductive material and the like onto a positive electrode core body, drying the applied slurry to form a positive electrode mixture layer, and then rolling this positive electrode mixture layer.

[0018] Examples of the conductive material contained in the positive electrode mixture layer include carbon-based particles such as carbon black (CB), acetylene black (AB), ketjen black, and graphite. These may be used alone, or two or more types may be used in combination.

[0019] Examples of the binder contained in the positive electrode mixture layer include fluorine-based resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide-based resins, acrylic resins, and polyolefin-based resins. These may be used alone, or two or more types may be used in combination.

[0020] The positive electrode active material includes, as a core capable of reversibly occluding and releasing Li, for example, a lithium-containing composite oxide. The lithium-containing composite oxide has a layered structure. The lithium-containing composite oxide may have, for example, a layered structure belonging to space group R-3m, a layered structure belonging to space group C2 / m, or the like. From the viewpoints of higher capacity, stability of the crystal structure and the like, the lithium-containing composite oxide preferably has a layered structure belonging to space group R-3m.

[0021] The lithium-containing composite oxide is, for example, secondary particles formed by aggregation of a plurality of primary particles. The particle diameter of the primary particles constituting the secondary particles is, for example, 0.05 μm to 1 μm. The particle diameter of the primary particles is measured as the diameter of a circumscribed circle in a particle image observed with a scanning electron microscope (SEM).

[0022] The volume-based median diameter (D50) of secondary particles of the lithium-containing composite oxide is, for example, 1 μm to 30 μm, preferably 3 μm to 20 μm. D50 refers to the particle diameter at which the cumulative frequency from the smaller particle diameter side reaches 50% in the volume-based particle size distribution, and is also called the median diameter. The particle size distribution of the composite oxide (Z) can be measured using a laser diffraction particle size distribution analyzer (for example, MT3000II manufactured by Microtrac Bell Co., Ltd.) with water as the dispersion medium.

[0023] The lithium-containing composite oxide may be represented by the general formula Li x Ni y M3 1-y O2 (0.9≦x≦1.4, 0.4≦y≦1, M3 is at least one element selected from the group consisting of Mn, Co, Al, and Fe). The mole fraction of each element constituting the lithium-containing composite oxide can be measured by, for example, inductively coupled plasma (ICP) emission spectrometry.

[0024] x representing the proportion of Li in the lithium-containing composite oxide preferably satisfies 0.9≦x≦1.4, and more preferably satisfies 1.1≦x≦1.4. When x<0.9, the battery capacity may decrease compared with the case where x satisfies the above range. When x>1.4, the charge-discharge cycle characteristics may be degraded compared with the case where x satisfies the above range.

[0025] y representing the ratio of Ni to the total number of moles of metal elements other than Li in the lithium-containing composite oxide preferably satisfies 0.4≦y≦1, and more preferably satisfies 0.7≦y≦0.95.

[0026] M3 (M3 is at least one element selected from the group consisting of Mn, Co, Al, and Fe) relative to the total number of moles of metal elements other than Li in the lithium-containing composite oxide is an optional component, and 1-y representing the proportion thereof satisfies 0≦1-y≦0.6.

[0027] On the surface of the lithium-containing composite oxide that is the core, the general formula M1 a M2F bA compound represented by (0.1≦a≦2.2, 2≦b≦6, M1 is one or more elements selected from the group consisting of Li, K, and Na, and M2 is one or more elements selected from the group consisting of transition metals and Al, Si, B, P, Sn, Ge, Sb, Bi, Mg, Ca, and Sr) is attached. This suppresses the decrease in discharge capacity at high rates and improves the rate characteristics of the secondary battery 10.

[0028] The core lithium-containing composite oxide surface is the surface of the secondary particles of the lithium-containing composite oxide. Furthermore, the compound may also be present inside the secondary particles of the lithium-containing composite oxide, i.e., on the surface of the primary particles. The presence of the compound on the surface of the primary particles further improves the rate characteristics of the secondary battery 10. The compound may exist as points covering at least a portion of the surface of the lithium-containing composite oxide, or it may cover the entire surface of the lithium-containing composite oxide. The particle size of the compound is, for example, 0.1 μm to 10 μm. The particle size of the compound is measured as the diameter of the circumscribed circle in the particle image observed by SEM. Specifically, the external shape of 20 randomly selected particles is determined, the major axis (longest diameter) of each of the 20 particles is calculated, and the average value of these is taken as the particle size of the compound.

[0029] General formula M1 a M2F b In a compound represented by (0.1≦a≦2.2, 2≦b≦6, M1 is one or more elements selected from the group consisting of Li, K, and Na, and M2 is one or more elements selected from the group consisting of transition metals and Al, Si, B, P, Sn, Ge, Sb, Bi, Mg, Ca, and Sr), it is preferable that M1 is Li and M2 is Ti, Zr, Si, B, or P. a TiF b It is more preferable that (0.1 ≤ a ≤ 2.2, 2 ≤ b ≤ 6), and particularly preferable that it be Li2TiF6. Since Li2TiF6 is a lithium ion conductive material, it is preferable to use it as a compound.

[0030] The compound is a deposit attached to the surface of the lithium-containing composite oxide core by dry mixing. For dry mixing, for example, mechanofusion may be used, or the lithium-containing composite oxide and the compound may be placed in a mortar and mixed by compression with a pestle.

[0031] The amount of compound adhering to the lithium-containing composite oxide is preferably 0.01 mol% to 1 mol%, more preferably 0.05 mol% to 0.5 mol%, and particularly preferably 0.1 mol% to 0.3 mol%. The presence of the compound on the surface of the lithium-containing composite oxide can be confirmed by X-ray diffraction (XRD). The amount of compound adhering to the lithium-containing composite oxide can also be measured by XRD.

[0032] Next, an example of a method for producing the positive electrode active material according to this disclosure will be described. For the sake of convenience of explanation, the surface of the lithium-containing composite oxide will be covered with a material of general formula M1 a M2F b A positive electrode active material to which a compound represented by (0.1≦a≦2.2, 2≦b≦6, M1 is one or more elements selected from the group consisting of Li, K, and Na, and M2 is one or more elements selected from the group consisting of transition metals and Al, Si, B, P, Sn, Ge, Sb, Bi, Mg, Ca, and Sr) is attached is defined as "composite oxide (Y)". In this disclosure, the positive electrode active material contained in the secondary battery 10 may be mainly composed of composite oxide (Y) and may be substantially composed only of composite oxide (Y). The positive electrode active material may also contain composite oxides other than composite oxide (Y) or other compounds to the extent that it does not impair the purpose of this disclosure.

[0033] The core lithium-containing composite oxide can be synthesized, for example, by adding a Li source to a Li-free composite compound (X), mixing them, and calcining them at 200°C to 1050°C. Examples of composite compounds (X) include composite oxides, hydroxides, and carbonate compounds containing Ni, Mn, etc. Examples of Li sources include LiOH. The lithium-containing composite oxide is washed with water using known methods and conditions, and the amount of LiOH remaining on the surface of the lithium-containing composite oxide after washing varies depending on the washing conditions. After washing, the lithium-containing composite oxide is dried and becomes a powder. The median diameter (D50) of the lithium-containing composite oxide can be adjusted by the calcination conditions, etc.

[0034] Next, the lithium-containing composite oxide powder is subjected to the general formula M1 a M2F b A compound represented by (0.1≦a≦2.2, 2≦b≦6, M1 is one or more elements selected from the group consisting of Li, K, and Na, and M2 is one or more elements selected from the group consisting of transition metals and Al, Si, B, P, Sn, Ge, Sb, Bi, Mg, Ca, and Sr) is added and dry-mixed. As a result, the compound adheres to the surface of the lithium-containing composite oxide, and a composite oxide (Y) is obtained. The particle size of the compound before dry mixing is, for example, 0.1 μm to 10 μm. The particle size of the compound is measured as the diameter of the circumscribed circle in the particle image observed by SEM. Specifically, the external shape of 20 randomly selected particles is determined, the major axis (longest diameter) of each of the 20 particles is determined, and the average value of these is taken as the particle size of the compound.

[0035] The amount of compound added to the lithium-containing composite oxide is preferably 0.01 mol% to 1 mol%, more preferably 0.05 mol% to 0.5 mol%, and particularly preferably 0.1 mol% to 0.3 mol%. Within this range, the compound can be attached to the surface of the lithium-containing composite oxide in an appropriate amount, thereby suppressing side reactions on the surface of the lithium-containing composite oxide. For dry mixing, for example, a mechanofusion method may be used, or the lithium-containing composite oxide and the compound may be placed in a mortar and mixed by pressing with a pestle. Dry mixing may be carried out, for example, at room temperature for 3 to 30 minutes.

[0036] [Negative electrode] The negative electrode 12 comprises, for example, a negative electrode core body such as a metal foil and a negative electrode composite layer provided on the surface of the negative electrode core body. The negative electrode core body can be made of a metal foil that is stable in the negative electrode potential range, such as copper, or a film with the metal arranged on its surface. The negative electrode composite layer includes, for example, a negative electrode active material and a binder. The negative electrode can be manufactured, for example, by coating a negative electrode composite slurry containing a negative electrode active material, a binder, etc., onto the negative electrode core body, drying it to form a negative electrode composite layer, and then rolling this negative electrode composite layer.

[0037] The negative electrode composite layer contains, as the negative electrode active material, a carbon-based active material that reversibly intercepts and releases lithium ions, for example. Suitable carbon-based active materials include natural graphite such as flake graphite, lumpy graphite, and clay-like graphite, as well as artificial graphite such as lumpy artificial graphite (MAG) and graphitized mesophase carbon microbeads (MCMB). In addition, a Si-based active material composed of at least one of Si and a Si-containing compound may be used as the negative electrode active material, and carbon-based active materials and Si-based active materials may be used in combination.

[0038] The binder included in the negative electrode composite layer may be fluororesin, PAN, polyimide, acrylic resin, polyolefin, etc., as in the positive electrode, but styrene-butadiene rubber (SBR) is preferred. Furthermore, the negative electrode composite layer preferably contains CMC or its salt, polyacrylic acid (PAA) or its salt, polyvinyl alcohol (PVA), etc. In particular, a combination of SBR and CMC or its salt, or PAA or its salt is preferred.

[0039] [Separator] A porous sheet with ion permeability and insulating properties is used as the separator. Specific examples of porous sheets include microporous thin films, woven fabrics, and nonwoven fabrics. Suitable materials for the separator include polyethylene, polyolefins such as polypropylene, and cellulose. The separator may have either a single-layer or multi-layer structure. A heat-resistant layer may be formed on the surface of the separator. [Examples]

[0040] The present disclosure will be further illustrated by the following examples, but the present disclosure is not limited to these examples.

[0041] <Example 1> [Synthesis of positive electrode active material] The median diameter (D50) is 17 μm, and the composition is LiNi 0.8 Mn 0.2 Li2TiF6 was added to a lithium-containing composite oxide of O2 at a rate of 0.12 mol%, and this mixture was placed in a mortar and compressed with a pestle. This dry mixing was carried out at room temperature for 15 minutes. As a result, LiNi 0.8 Mn 0.2 A positive electrode active material was obtained in which Li2TiF6 was attached to the surface of a lithium-containing composite oxide represented by O2. Furthermore, it was confirmed by XRD that Li2TiF6 was attached to the surface of the lithium-containing composite oxide, and that its amount was 0.12 mol%, the same as the added amount.

[0042] [Fabrication of the positive electrode] The above-mentioned positive electrode active material, acetylene black, and polyvinylidene fluoride (PVdF) were mixed in a solid content mass ratio of 96.3:2.5:1.2, an appropriate amount of N-methyl-2-pyrrolidone (NMP) was added, and the mixture was kneaded to prepare a positive electrode slurry. This positive electrode slurry was applied to both sides of a positive electrode core made of aluminum foil, the coating was dried, the coating was rolled using a roller, and the electrode was cut to a predetermined electrode size to obtain a positive electrode in which a positive electrode slurry layer was formed on both sides of the positive electrode core.

[0043] [Preparation of non-aqueous electrolytes] Fluoroethylene carbonate (FEC), ethylene carbonate (EC), and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 1:1:6 to obtain a non-aqueous solvent. LiPF6 was dissolved in this non-aqueous solvent at a concentration of 1.0 mol / L to obtain a non-aqueous electrolyte.

[0044] [Preparation of test cells] Lead wires were attached to the positive electrode and the lithium metal counter electrode, respectively, and the electrode body was fabricated by arranging the positive electrode and the counter electrode opposite each other via a polyolefin separator. This electrode body and the non-aqueous electrolyte were sealed in an outer casing made of aluminum laminate film to create a test cell.

[0045] [Evaluation of charging capacity, discharging capacity, charge / discharge efficiency, and average discharge voltage] Under a temperature of 25°C, constant current charging was performed at a constant current of 0.2C until the cell voltage reached 4.5V, and then constant voltage charging was performed until the current value was 0.02C at 4.5V. Subsequently, constant current discharge was performed at a constant current of 0.2C until the cell voltage reached 2.5V. The charging capacity, discharging capacity, and average discharge voltage were measured during this process. The charge / discharge efficiency was calculated by dividing the discharge capacity by the charging capacity.

[0046] [Evaluation of rating characteristics] Under a temperature of 25°C, constant current charging was performed with a constant current of 0.2C until the cell voltage reached 4.5V, and then constant voltage charging was performed until the current value was 0.02C at 4.5V. Subsequently, constant current discharge was performed with a constant current of 0.2C until the cell voltage reached 2.5V, and the discharge capacity C1 at 0.2C was measured. Next, constant current charging was performed with a constant current of 0.5C until the cell voltage reached 4.5V, and then constant voltage charging was performed until the current value was 0.02C at 4.5V. Subsequently, constant current discharge was performed with a constant current of 1C until the cell voltage reached 2.5V, and the discharge capacity C2 at 1C was measured. The rate characteristics were calculated using the following formula. Rate characteristic (%) = C2 / C1 × 100

[0047] <Example 2> In the synthesis of the positive electrode active material, the test cell was prepared and evaluated in the same manner as in Example 1, except that the D50 of the lithium-containing composite oxide was 5 μm and the amount of Li2TiF6 added was changed to 0.25 mol%.

[0048] <Comparative Example 1> In the synthesis of the positive electrode active material, the test cell was prepared and evaluated in the same manner as in Example 1, except that Li2TiF6 was not added and the lithium-containing composite oxide was used directly as the positive electrode active material.

[0049] <Comparative Example 2> In the synthesis of the positive electrode active material, the test cell was prepared and evaluated in the same manner as in Example 2, except that Li2TiF6 was not added and the lithium-containing composite oxide was used directly as the positive electrode active material.

[0050] Table 1 summarizes the charging capacity, discharging capacity, charge / discharge efficiency, average discharge voltage, and rate characteristics of the test cells for the examples and comparative examples. Table 1 also shows the median diameter (D50) of the lithium-containing composite oxide, the composition of the additives, and the amount of additives added.

[0051] [Table 1]

[0052] The test cells in Examples 1 and 2 exhibited higher rate characteristics compared to the test cells in Comparative Examples 1 and 2, respectively. Furthermore, the test cells in the examples showed performance comparable to the comparative examples in terms of charge capacity, discharge capacity, charge / discharge efficiency, average discharge voltage, and rate characteristics. [Explanation of symbols]

[0053] 10 Secondary battery, 11 Positive electrode, 12 Negative electrode, 12a End of winding, 13 Separator, 14 Electrode body, 15 Outer casing, 16 Sealing body, 17,18 Insulating plate, 19 Positive electrode lead, 20 Negative electrode lead, 21 Grooved section, 22 Filter, 23 Lower valve body, 24 Insulating member, 25 Upper valve body, 26 Cap, 26a Opening, 27 Gasket

Claims

1. A method for producing an active material for a non-aqueous electrolyte secondary battery, comprising a core which is a lithium-containing composite oxide capable of reversibly intercalating and deintercalating Li, and a compound attached to the surface of the core, The core has a layered structure and the general formula Li x Ni y M3 1-y O 2 (It is represented as 0.9 ≤ x ≤ 1.4, 0.7 ≤ y ≤ 1, and M3 is at least one element selected from the group consisting of Mn, Co, Al, and Fe), The above compound has the general formula M1 2 TiF 6 (M1 is represented by one or more elements selected from the group consisting of Li, K, and Na) The amount of the compound adhering to the lithium-containing composite oxide is 0.1 mol% to 0.3 mol%, A method for producing an active material for a non-aqueous electrolyte secondary battery, comprising dry mixing the lithium-containing composite oxide and the compound.

2. The method for producing an active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein M1 is Li.

3. The method for producing an active material for a non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein the compound is a deposit attached to the surface of the core by dry mixing.

4. A method for manufacturing a non-aqueous electrolyte secondary battery, comprising an electrode containing an active material for a non-aqueous electrolyte secondary battery manufactured by the manufacturing method described in any one of claims 1 to 3, a counter electrode for the electrode, and an electrolyte.

Citation Information

Patent Citations

  • Surface-modified lithium-containing composite oxide particles, positive electrode using surface-modified lithium-containing composite oxide particles, and nonaqueous electrolyte secondary battery

    WO2014104234A1